Strategi Pelestarian Tari Remo Oleh Sanggar Seni Denandar di Kota Batu Jawa Timur - Aulia Nurulita; Lesa Paranti (Jurnal Riset Rumpun Seni, Desain dan Media, 2026)
T This study aims to examine the preservation strategies of Remo Dance at Denandar Art Studio, Batu City, by referring to the four elements of cultural advancement, namely protection, development, utilization, and documentation. The study employed a qualitative method with a phenomenological approach to understand the experiences and preservation practices carried out by artists at the community level. Data were collected through in-depth interviews, non-participant and direct observations, and documentation studies, and were subsequently analyzed thematically. The findings indicate that preservation through regular training and the transmission of dance techniques constitutes the most dominant element, while documentation and legal protection remain limited. These findings highlight the strategic role of art studios in cultural transmission and demonstrate the need to strengthen documentation and policy support to ensure the sustainability of Remo Dance preservation in a contemporary cultural context. These efforts contribute to the regeneration of young dancers, increased public appreciation, and the strengthening of local cultural identity. Furthermore, the active involvement of studio managers, instructors, and students plays an important role in maintaining the continuity of traditional artistic practices amid the development of popular culture. This study emphasizes the significant role of art studios as cultural preservation institutions, particularly for Remo Dance, within the dynamics of modern society.